Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1213/ane.0b013e3181957d84
|View full text |Cite
|
Sign up to set email alerts
|

Current Threshold for Nerve Stimulation Depends on Electrical Impedance of the Tissue: A Study of Ultrasound-Guided Electrical Nerve Stimulation of the Median Nerve

Abstract: Our results demonstrate an inverse relationship between impedance measurements and current thresholds and suggest that current settings used for nerve stimulation may require adjustment based on the tissue type. Further studies should be performed to investigate the clinical impact of our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 19 publications
0
30
0
3
Order By: Relevance
“…Typical examples are measurements and stimulations in anaesthesiology and neurology (Tsui et al 2004) (Sauter et al 2009) (King et al 1998) The goal for this study was to develop a method to describe the sensitivity field for needle electrodes in an ongoing project concerning a new method for anatomical needle positioning in the clinic ). The description of sensitivity field will furthermore be important in an ongoing resuscitation project using bioimpedance measurements to confirm intravascular needle position.…”
Section: Introductionmentioning
confidence: 99%
“…Typical examples are measurements and stimulations in anaesthesiology and neurology (Tsui et al 2004) (Sauter et al 2009) (King et al 1998) The goal for this study was to develop a method to describe the sensitivity field for needle electrodes in an ongoing project concerning a new method for anatomical needle positioning in the clinic ). The description of sensitivity field will furthermore be important in an ongoing resuscitation project using bioimpedance measurements to confirm intravascular needle position.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has also been suggested that electrical impedance influences the threshold current required when using nerve stimulation. 12,[15][16][17] Given that peripheral nerve blocks are generally performed with the guidance of nerve stimulation and that currently available stimulators display resistance, this study serves as a reminder for clinicians to utilize this information for such uses as detection of intravascular placement of the stimulating electrode. The adjuvant use of ultrasound also benefits from a test injection of D5W, given that the observed spread enables prediction of the local anesthetic spread without adding to the total local anesthetic volume or altering the threshold currents used for nerve stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…This was done recording the voltage drop across a RC low pass filter made with the parallel combination of a 10 Ω resistor and 2.2 μF capacitor (cutoff frequency = 7.2 kHz). The results show that the current sources implemented were able to generate a low frequency current peak value of 2.7 mA in the cathodal phase and a peak value of 2.8 mA in the anodal phase, which is enough to electrically stimulate nerves [10]. The calculated charge shows that the circuit was able to inject over 0.22 μC in the cathodal phase of the stimulation and that this charge was balanced during the anodal phase.…”
Section: Complete Circuit Architecturementioning
confidence: 93%